Comportamiento agronómico y valoración nutricional de la asociación de clitoria (clitoria ternatea) con pasto saboya (panicum maximun) y pasto brachiaria decumbens (brachiaria decumbens) - García Miranda, Edmundo Flavio (2011)
In the property "María" of the Technical State University of the canton Quevedo, county of Ríos was determined the agronomic "Behavior and nutritional value of the association of Clitoria (Clitoria ternatea) with grass Saboya (Panicum maximun) and grass Brachiria (Brachiaria decumbens)" in different states of maturity, where they took as objectives to analyze the agronomic behavior of the gramineous-leguminous associations and to carry out the analyses bromatológicos to determine the nutritional value, using a design of complete blocks at random (DCA). In the simple effect of the grass, the association Clitoria with grass Saboya obtained the best indexes in the variables forage (327,22 g) weight, shaft (157,22 g) weight and relationship leaves aérea:parte radicular (1,44). The best results for the variables root (567,25 g) weight, weight of leaves (45,33 g) and relationship hoja:talllo (0,52). In the simple effect of the ages the highest results to the 80 days were reported in the variables forage weight, weight of leaves, shaft weight, relationship hoja:tallo and relationship leaves aérea:parte radicular. To the 140 days the highest values registered in the variable root weight. In the interaction of the associations for the ages, the best indexes in forage (388,4 kg) weight, shaft (183,5 kg) weight and relationship leaves aérea:parte radicular (1,95 kg), they register to the 80 and 110 days in the association of Clitoria with the grass Saboya; and the best root (1020,35 kg) weight, weight of leaves (76,05 kg) and relationship hoja:tallo (0,67) with the association of Clitoria with grass Brachiaria to the 80 and 140 days. The protein greater levels were obtained with the association of Clitoria with grass Brachiria to the 80 and 110 days with the 10,12 and 8,50%. And the lowest fiber level is reported in the association of C. ternatea with grass Saboya to the 110 days with 19,10%. For the composition microbiológica, the tall populations at the 80 of bacterias (3,9 x 10 5) actinomicetes (4,7 x 10 6), solubilizadores of P (3,5 x 10 4), and fixers of N asimbiótico (1,6 x 10) showed up with the association of Clitoria and grass Saboya; and to the 140 days the biggest population of bacterias (9,8 x 105) mushrooms (3,1 x 104) and celulolíticos (2,1 x 106) in the association with the grass Brachiria. The bigger than colonization percentage and endófitos density showed up to the 80 days in the association of Clitoria with the grass Saboya, and to the 140 days with the association of Clitoria with grass Brachiaria. For the obtained results you confirmed the outlined hypothesis: "The gramineous-leguminous association Clitoria (Clitoria ternatea) more grass Saboya (Panicum maximun) will show the biggest production of biomass in the different states of maturity" and the hypothesis "The nutritious value of the gramineous-leguminous association Clitoria was discarded with grass Saboya for the two court ages it will be superior."